The Role of Adipokines in Cardiovascular Pathology - Podzolkov , Valery; Pokrovskaya, Anna; Bazhanova , Ulyana; Vargina , Tatyana; Knyazeva , Svetlana Anatolievna; Vanina , Daria (Open Access Macedonian Journal of Medical Sciences, 2021)
The recent decades saw a steady growth of obesity incidence worldwide. Obesity is an independent risk factor for cardiovascular diseases (CVDs) and type 2 diabetes mellitus and is also associated with a shorter life expectancy. Not only hemodynamic but also hormone metabolic processes, arising from excessive accumulation of adipose tissue in human body, underlie the development of CVDs. Adipose tissue has now been proved to be a hormone-active substrate. Studies of the influence of adipokines will bring us closer to understanding cardiovascular pathogenesis and help personalize prophylactic strategies.